ANALISIS SWOT DALAM PENGEMBANGAN DESA WISATA DIUKUR DARI TINGKAT KESEJAHTERAAN MASYARAKAT(Studi Kasus Desa Wisata Lontar Sewu Hendrosari) - Safira Putri Rahmadana (CURVE: Journal of Economic, Business and Accounting, 2026)
This study uses SWOT Analysis. This analysis is based on reasoning that can simultaneously minimize weaknesses and threats while still maximizing strengths and opportunities. The researcher also uses the Human Development Index theory to measure the community's welfare after the development of Lontar Sewu Tourism Village, in order to support the findings of the SWOT analysis. Based on the research findings, Lontar Sewu Tourism Village is classified as class I for both internal and external factors (positive, positive). This indicates that the development of Lontar Sewu Tourism Village is strong and has potential, and the strategic recommendations provided are aggressive. Furthermore, the welfare level of the residents of Hendrosari Village also shows changes and is gradually increasing in accordance with what is stated in the Human Development Index theory, namely the Long and Decent Life Indicator, the Knowledge Indicator, and the Decent Standard of Living Indicator. As for the suggestions that can be given as guidelines to the village government and tourism managers, they are to provide regular educational training for business owners, enhance marketing both directly and indirectly, and be able to predict opportunities for high-value products that can be developed and innovated to be able to face competition among tourist destinations.